Epidemiology of fractures and care in male collegiate Taekwondo athletes by weight classes - Wang, Haifang; Yoo, Sangcheol; Song, Munku (International Journal of Sports Medicine, 2025)
The purpose of this study was to examine the occurrence of fracture injuries and post-fracture management practices by weight classes. A total of 127 male collegiate Taekwondo athletes (64 lightweight athletes and 63 heavyweight athletes) participated in this study. The athletes were classified into lightweight and heavyweight based on their respective competition weight divisions. Logistic regression was used to estimate the odds ratios and 95% confidence intervals. Athletes had experienced fractures to 54.3%. Athletes were more likely to experience fractures during training and defensive movements. Of the fractures reported, 31.9% necessitated surgical intervention. Although 65.1% of the athletes were primarily concerned about the possibility of reinjury, only 36.2% received specialized rehabilitation. The heavyweight athletes had a higher prevalence of fractures (odds ratio=2.40 and 95% confidence interval=1.17–4.90) than the lightweight athletes. The heavyweight athletes had a higher prevalence of fractures during the competition (odds ratio=4.83 and 95% confidence interval=1.54–15.17), in offensive situations (odds ratio=4.67 and 95% confidence interval=1.38–15.99), and in the lower limbs (odds ratio=3.84 and 95% confidence interval=1.12–13.14) than the lightweight athletes. The current evidence that fractures are common in Taekwondo athletes and that fracture patterns may differ between heavyweight and lightweight athletes highlights the need for tailored prevention strategies based on weight classes.
Keywords: sport injuries; sparring sports; collegiate athletes; fractures; martial arts